ANALISIS KAFEIN MINUMAN BERENERGI BERMERK MENGGUNAKAN METODE SPOT-TEST DAN IODOMETRI - Safrina; Desi Ratna Dewi (Lembaga Riset dan Inovasi Kreyat Center, 2024)
Energy drinks contain one or more components the body can easily and quickly absorb to provide energy, with or without approved dietary additives such as caffeine. This study aims to analyze the caffeine levels in three branded energy drinks circulating in the district of Aceh Besar using spot-test and iodometric titration methods. Sampling was carried out using purposive sampling, where selected samples of branded energy drinks were not registered with the Food and Drug Monitoring Agency (BPOM). Based on the results of the spot-test analysis, the three energy drinks branded positively (+) contain caffeine. Through analysis of the iodometric titration method, the concentration was 195,43±2,03, 49,99±0,01, and 60,60±2,1 mg/serving, respectively. Only sample B has caffeine levels by SNI 01-6684-2002 and BPOM standards, which state that caffeine levels in energy drinks should not exceed 50 mg/serving and 150 mg/day.